P125: Low dose intravenous ketorolac in renal colic, a pilot randomized controlled trial. (May 2020) - Chao, J.; Brasher, P.; Cheung, K.; Sharma, R.; Badke, K.; Hohl, C.
Abstract : Introduction: Non-steroidal anti-inflammatory drugs (NSAIDs) are first-line analgesics for emergency department (ED) patients with renal colic. Lower doses of intravenous (IV) ketorolac may provide similar pain relief to standard dosing in patients with acute pain. Patients with renal colic may be at increased risk of acute kidney injury; exposing them to lower doses of NSAIDs may put them at lower risk while providing equally effective analgesia. We conducted a pilot study to determine the feasibility of a randomized trial comparing the effectiveness and safety of low with standard ketorolac dosing in ED patients with suspected renal colic. The primary objective was to demonstrate the ability to achieve an enrolment target of 2 patients per week. Methods: We enrolled a convenience sample of adults presenting to an academic urban ED with unilateral flank pain suspected to be renal colic. We randomized patients to 10 mg (low dose, intervention) or 30 mg (standard dose, control). Participants, treating physicians and nurses, and researchers were blinded to treatment allocation. Our main feasibility outcome was the recruitment rate. Secondary outcomes were changes in pain scores (0-10) at 30 and 120 minutes post-ketorolac administration, vital signs, adverse events and ED length of stay. Results: We approached 82 patients, of whom 47 (57.3%) were eligible. Of these, 36 consented to participating and 30 were randomized. The proportion of screened patients who were enrolled was 36.6% (30/82). We completed enrolment over a 21-week period, with an average recruitment rate of 1.5 patients/week (range 0-4). The average baseline pain score for all participants was 6.9 (SD = 2.1). At 30 minutes post-ketorolac administration, the low dose group had a mean pain reduction of 2.0 points compared to a pain reduction of 1.7 in standard dose group (difference = 0.3, 90% CI: -0.7 to 1.4). Conclusion: These preliminary results support the possibility that low dose ketorolac may be efficacious in this patient population. We did not meet our target recruitment of 2 patients per week as this was primarily due to restricted recruitment hours. To successfully conduct a larger trial, we would need to expand both recruitment hours and the number of sites.